New Approaches To Cleaning Exhaust Gases Of Internal Combustion Engines - Ilkham Z. Nasirov; Dilnoza T. Kozibolaeva; Saidolimkhon Z. Abbasov (Zien Journals, 2023)
By adding 5-6% of an alternative fuel - Brown's gas to the main fuel for the complete combustion of the fuel used in vehicles, in the cylinders of internal combustion engines, it was possible to reduce fuel consumption by 25-35%, and the amount of carbon dioxide by an average of 60-70% . Due to the use of a new collapsible spark plug instead of a conventional spark plug, it was possible to reduce fuel consumption by 15-30%, the amount of carbon monoxide by 40-50%, the amount of unburned hydrocarbons by 30-40%.
Keywords: toxic component; ecology; fuel consumption; exhaust gases